Laparoscopic Surgery for Solid Pseudopapillary Pancreatic Tumor in a Pediatric Patient - Sartori, Paola V; Miranda, Angelo; Costanzi, Andrea T; Valenti, Francesco; Prada, Massimo; Leone, Biagio E; Maggioni, Dario (JOP. Journal of the Pancreas, 2012)
Context Solid pseudopapillary pancreatic tumor is a rare pancreatic malignancy affecting mainly young females and quite often pediatric population. In literature there is no consensus about its management especially regarding surgical approach. We report our experience in treating one case occurred in a pediatric patient. Case report A 14-year-old female was admitted at Pediatric Department complaining of abdominal pain in lower quadrants associated to repeated vomiting. Biochemistry was normal except for leucocytosis. Abdominal ultrasound scan shown a 7 cm isoechoic epigastric lesion lateral but contiguous to the stomach and gallstones. The patient was submitted to a nuclear magnetic resonance which shown a 76 mm round lesion involving the pancreatic tail with sharp margins, without contrast enhancement and with fibrolipidic content. She underwent laparoscopic spleen preserving distal pancreatectomy and synchronous cholecystectomy. Postoperative course was uneventful and she was discharged after ten days. At histology the neoplasm proved to be a solid pseudopapillary pancreatic tumor mainly composed by round or polygonal cells with pseudopapillary areas. It stained positively for cytokeratin, vimentin, CD10 and had progesterone receptors. There was no vascular invasion. The patient is currently disease free after 12 months. Conclusions Since these tumors occur mainly in young females, laparoscopic resection, especially for lesions of the distal pancreas, is a valid treatment option provided safe margins can be achieved. In facts this neoplasm has been recently upgraded from borderline pancreatic lesions to malignancies.